2004
DOI: 10.1111/j.1744-7348.2004.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Oidium neolycopersici development on host and non‐host plant species and their tissue defence responses

Abstract: SummaryDetailed studies of the infection processes of Oidium neolycopersici (tomato powdery mildew) and plant tissue responses were carried out on 10 Lycopersicon spp. accessions and one of each species of Cucumis sativus, Datura stramonium, Lactuca sativa, Petunia hybrida and Pisum sativum with different levels of resistance. Germination of O. neolycopersici conidia was not inhibited by the host plant. However, in the early stages of O. neolycopersici infection significant differences in conidial germ tube de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 33 publications
2
38
0
8
Order By: Relevance
“…Also for the interaction between non-host plants and O. neolycopersici, it was concluded (Huang et al 2000a) that resistance was not based on inhibition of formation of primary haustorium, but on post-haustorial HR and another type of nonhypersensitive resistance. This was confirmed by Mieslerová et al (2004) who found no effective prehaustorial resistance. For a better understanding of this phenomenon we need a more detailed study of its biochemical and molecular background.…”
Section: Non-host Resistancesupporting
confidence: 70%
See 4 more Smart Citations
“…Also for the interaction between non-host plants and O. neolycopersici, it was concluded (Huang et al 2000a) that resistance was not based on inhibition of formation of primary haustorium, but on post-haustorial HR and another type of nonhypersensitive resistance. This was confirmed by Mieslerová et al (2004) who found no effective prehaustorial resistance. For a better understanding of this phenomenon we need a more detailed study of its biochemical and molecular background.…”
Section: Non-host Resistancesupporting
confidence: 70%
“…The second stage plant-pathogen interaction is represented by colonisation of plant tissue, including cell responses. Experiments by Mieslerová et al (2004) showed that O. neolycopersici stopped its development on non-host plants (Lactuca sativa and Pisum sativum) early after the first appressoria and haustoria formed in plant cells. Huang et al (2000a) observed intensive cell necrosis (hypersensitivity) in lettuce after inoculation with O. neolycopersici, which was in contrast with the observations of Mieslerová et al (2004).…”
Section: Non-host Resistancementioning
confidence: 99%
See 3 more Smart Citations